RESERVOIR CHARACTERIZATION, COMPARTMENTALIZATION, AND RESERVE ESTIMATION OF A1-3, A1-8 AND A1-81 RESERVOIR INTERVALS, SUKIT FIELD, KAMPUNGBARU FORMATION, KUTAI BASIN, EAST KALIMANTAN PROVINCE - Tonggo Samuel, Gerald
Sukit field is one of the oil field, which is located in Mahakam block, Kutai Basin, East Kalimantan. Sukit field has an area of 44,5 km2, which has been producing for 45 years. Research interval are reservoirs A1-3, A1-8, and A1-81, in Kampungbaru Formation. This research was carried out to determine the depositional environment, facies distribution, reservoir geometry, formation evaluation, and petrophysical property distribution of each reservoir intervals. Reserve estimation was analyzed to find the oil reserve that still can be produced in Sukit Field from the reservoir interval. The data used in the research are core report data, log data from 392 wells, and surface seismic data as well as pressure and fluid test reports the reservoir intervals. Core report data analysis in the intervals near reservoirs A1-3, A1-8, and A1-81 shows three lithofacies, bioturbated sandstones (Sb), cross laminated sandstones (Scb), and bioturbated claystone (Cb). These lithofacies formed a facies association of distributary channel. Core report data then matched with electrofacies data resulting another electrofacies can be ommited, belong to the facies association of crevasse splay. Based on the core, sedimentary structure, and electrofacies analyses, reservoir intervals are interpreted as parts of a delta plain. Analysis of facies distribution was carried out based on the model of a delta plain and controlled by the NW-SE regional depositional direction. Petrophysical property distribution analysis was then performed on the modeled facies. The calculation of the estimated reserve shows that the oil volumes from the reservoir A1-3 is 0,795 MMBO, reservoir interval A1-8 is 0,607 MMBO, and reservoir interval A-81 is 5,796 MMBO.